ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENGELUARAN PEMERINTAH DAN INFLASI TERHADAP INVESTASI DI SUMATERA BARAT - Martilova, Novera; Doni, Amsah Hendri (IAIN Batusangkar, 2020)
This research aims to analyze the effect of Economic Growth, Government Expenditures and Inflation on Investment in West Sumatra from 2001-2015. The type of this research is descriptive and associative; the data analyses used are descriptive analysis and inductive analysis. The analysis model used is the Ordinary Last Square (OLS) Method. The results of the study concluded that (1) Economic growth has a significantly positive effect on investment in West Sumatra. (2) Government Expenditures have a significant positive effect on Investment in West Sumatra. (3) Inflation has a negative significant effect on investment in West Sumatra. (4) Simultaneously, Economic Growth, Government Expenditures and Inflation have a significant effect on Investment in West Sumatra at 97.8% for the period of 2001-2015.